2012
DOI: 10.3109/01480545.2012.737802
|View full text |Cite
|
Sign up to set email alerts
|

The effect of granulocyte colony-stimulating factor administration on carbon monoxide neurotoxicity in rats

Abstract: Granulocyte colony-stimulating factor (G-CSF) is considered to be a novel neuroprotective agent. Beneficial effects have been demonstrated by administrating G-CSF in different experimental stroke models. In this study, we evaluated the efficacy of G-CSF therapy on carbon monoxide (CO) neurotoxicity in rats exposed to acute CO poisoning. Immediately after exposure to 3,000 ppm of CO for 60 minutes, 50, 100, and 150 µg/kg of G-CSF or normal saline were administered to rats. Rats were sacrificed after 24 hours fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In a pilot study, we showed that COHb levels were reduced to 60% under these conditions. In another study, we have shown that examining brain tissue slides of CO‐poisoned rats showed histopathological changes induced by CO poisoning (Ghorbani et al, ) indicating an efficient CO intoxication.…”
Section: Discussionmentioning
confidence: 90%
“…In a pilot study, we showed that COHb levels were reduced to 60% under these conditions. In another study, we have shown that examining brain tissue slides of CO‐poisoned rats showed histopathological changes induced by CO poisoning (Ghorbani et al, ) indicating an efficient CO intoxication.…”
Section: Discussionmentioning
confidence: 90%
“…However, peripheral administration of G-CSF has shown neuroprotective properties in carbon monoxide poisoning (Ghorbani et al, 2013), a Parkinson’s disease model (Frank et al, 2012), in focal cerebral ischemia (Hong et al, 2012), and in a TBI model (Acosta et al, 2014). Thus, a more robust response in G-CSF levels could be neuroprotective and so correlate with a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It also mobilizes stem cells and several studies indicate that it has neuroprotective properties after its peripheral administration (Frank et al, 2012; Ghorbani et al, 2013; Hong et al, 2012). For example, G-CSF is neuroprotective against carbon monoxide toxicity and ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…A diverse group of other substances has been tested in animal studies and has shown possible benefit, including granulocyte colony-stimulating factor, nimodipine, fructose diphosphate, hyperoxygenated solution and edaravone [57-60]. An even more diverse group of substances has been shown to be effective in hypoxic/reperfusion injury.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%